The Energy Performances of a Ground-to-Air Heat Exchanger: A Comparison Among Köppen Climatic Areas - Diana D’Agostino; Francesco Esposito; Adriana Greco; Claudia Masselli; Francesco Minichiello (Energies, 2020)
In this paper the energy performances carried out by an investigation conducted on a Heating, Ventilation and Air Conditioning (HVAC) system, composed by an Air Handling Unit (AHU) for the primary air coupled with a horizontal-pipes Ground-to-Air Heat eXchanger (GAHX) and fan-coil units, for an office building, supposed to be placed in four different cities (Rio de Janeiro, Dubai, Naples, Ottawa) belonging to four different worldwide climatic areas, according to the Köppen climate classification. The investigation is performed by means of a two dimensional numerical model, experimentally validated, of an GAHX solved with finite element method. The results introduced in this paper are carried out by varying the length of the pipes and the air flow velocity; thus, also the number of tubes forming the GAHX is varied since the volumetric flow rate to be provided to the AHU must be kept constant. The energy performances of the above-mentioned HVAC system are analyzed, both in summer and in winter operation modes. Specifically, the reduction of the power of the heating and cooling coils in the AHU due to the pre-treatment of the air operated by the GAHX, the efficiency of the GAHX and the inlet-outlet temperature span are evaluated through a sensitivity analysis. These results lead to say that an GAHX for the geothermal pre-treatment of the air to be introduced into the AHU is energetically very convenient since it leads total thermal power savings in all the investigated cities, that makes this solution competitive. Specifically the best value of power reduction (61.5%) for a 100 m pipe-length GAHX is obtained in Ottawa, a city belonging to continental climate zone. The worst results in terms of power reduction are registered in Rio de Janeiro, a city belonging to the tropical or equatorial climates: this reduction, for a 100 m pipe-length ground to air heat exchanger, is 23.9%.